1999
DOI: 10.1146/annurev.nutr.19.1.17
|View full text |Cite
|
Sign up to set email alerts
|

PSYCHOSOCIAL CORRELATES OF DIETARY INTAKE: Advancing Dietary Intervention

Abstract: Psychosocial variables that predict dietary behavior become important targets for change in nutrition education programs. Psychosocial variables in models with higher predictability provide more effective levers to promote healthy dietary change. A review of the literature on models with psychosocial variables predicting dietary fat and fruit and vegetable consumption revealed generally low predictiveness, R2 < 0.3 (where R2 is the squared multiple correlation of the statistical model). No single theory provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
272
3
15

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(312 citation statements)
references
References 75 publications
22
272
3
15
Order By: Relevance
“…Baranowski et al reports 37 that modest explanation of variance in dietary intake is the norm. Further, although FFQs are considered to be valuable in the clarification of major dietary patterns in both adults 38 and children, 39 it is possible that low variance might be explained by difficulties in accurately assessing all aspects of dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…Baranowski et al reports 37 that modest explanation of variance in dietary intake is the norm. Further, although FFQs are considered to be valuable in the clarification of major dietary patterns in both adults 38 and children, 39 it is possible that low variance might be explained by difficulties in accurately assessing all aspects of dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial environmental model explained most of the variance in fruit intake in both boys (47%) and girls (42%). In most previously conducted studies, explained variances of less than 30% were found (Baranowski et al, 1999;Neumark-Sztainer et al, 2003). Differences in results can be caused by differences in measures and analysing methods.…”
Section: Determinants Of Eating Behaviours In Adolescentsmentioning
confidence: 91%
“…Some of these factors are endogenous to the individual child, but others are environmental. The latter include the foods made available to children inside and outside the home and the modelling of food behaviours by caregivers, especially parents (Crockett & Sims, 1995;Birch & Fisher, 1998;Baranowski et al, 1999;Birch, 1999). Studies show that current eating environment in developed countries fosters food preferences and food selections inconsistent with healthy dietary guidelines, thus promoting excess weight gain and obesity (Crockett & Sims, 1995;Birch, 1999;St-Onge et al, 2003).…”
Section: Introductionmentioning
confidence: 99%